Control of the truncation errors for generalizedFdistributions - Nunes, Célia (2020)
Submitted by FERREIRA (dario@ubi.pt) on 2020-02-05T18:13:56Z No. of bitstreams: 1 2012 - Control of the truncation errors for generalized F distributions.pdf: 122092 bytes, checksum: 1bdad4b397149583e1003d178859064b (MD5)